2023
DOI: 10.1080/22423982.2023.2194141
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tourniquet pressure over military winter clothing and a short review of combat casualty care in cold weather warfare

Abstract: Cold weather warfare is of increasing importance. Haemorrhage is the most common preventable cause of death in military conflicts. We analysed the pressure of the Combat Application Tourniquet® Generation 7 (CAT), the SAM® Extremity Tourniquet (SAMXT) and the SOF® Tactical Tourniquet Wide Generation 4 (SOFTT) over different military cold weather clothing setups with a leg tourniquet trainer. We conducted a selective PubMed search and supplemented this with own experiences in cold weather medicine. The CAT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Even though various scholars have executed ET application studies, most of these have been conducted in laboratory settings or at ambient temperatures. [24][25][26][27][28][29] The Antarctic field conditions of humidity levels, windchill impact, Zodiac movements, and cold weather conditions present a considerable obstacle when striving to replicate experimental outcomes. 22,23 Despite these challenges, the participants could SA most of the ET in the upper and lower extremities donned in the AES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though various scholars have executed ET application studies, most of these have been conducted in laboratory settings or at ambient temperatures. [24][25][26][27][28][29] The Antarctic field conditions of humidity levels, windchill impact, Zodiac movements, and cold weather conditions present a considerable obstacle when striving to replicate experimental outcomes. 22,23 Despite these challenges, the participants could SA most of the ET in the upper and lower extremities donned in the AES.…”
Section: Discussionmentioning
confidence: 99%
“…Their study demonstrated the achievable vascular occlusion pressure, proving the feasibility of this technique. 27 The authors acknowledge the difficulties in measuring the effectiveness of ETs for vascular occlusion pressure in the Antarctic field conditions of the study. Such challenges may include but are not limited to environmental variables, individual differences, and technical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Lechner et al [ 42 ] compared three candidate tourniquet systems for use over clothing in field conditions. The study suggested that maximum pressure is dependent on the clothing characteristics and emphasised the need to test such equipment under simulated Arctic conditions in the laboratory, as well as under field conditions as sub-zero temperatures could render components of such systems inoperable.…”
Section: Freezing Cold Injuries and Their Treatmentmentioning
confidence: 99%